Pemodelan Vaksin Salmonellosis Ayam Domestik (Gallus gallus domesticus) berbasis Ekstrak Kasar LPS Salmonella typhimurium - Rizky Surya Wijaya (FAKULTAS MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2026)
Salmonellosis is a zoonotic disease with infections not limited to humans, but can also affect wild and domestic animal species. As many as 85% of salmonellosis cases are caused by contaminated food, especially in poultry products. Some of the salmonellosis vaccine products produced from S. typhimurium are live attenuated, invactive vaccines, and ghost cells. We conduct research on Salmonellosis vaccine based on S. typhimurium. The sample was in the form of female domestic chickens of the AKY strain which was divided into 3 groups, namely the control group injected with PBS, treatment group 1 injected with LPS with adjuvant with a concentration of 0.5 mg/kg and treatment group 2 injected with LPS with adjuvant with a concentration of 1 mg/kg. The results obtained were chicken body temperature measurement at 1, 3, and 5 weeks treatment groups had significantly different results from the control group (P = 0.000). The results of IL-6 and IgG measurements in both the treatment group and the control group also differed significantly (p = 0.000). These results illustrate that LPS crude extract of S. typhimurium has the potential to be developed into an LPS-based salmonellosis vaccine.
Finalisasi Juli 2026 hasyim
Keywords: Gallus gallus domesticus; Vaccine; LPS; Salmonella typhimurium